Evaluating the deHoffmann‐Teller Cross‐Shock Potential at Real Collisionless Shocks. Issue 8 (1st August 2021) - Schwartz, Steven J.; Ergun, Robert; Kucharek, Harald; Wilson, Lynn; Chen, Li‐Jen; Goodrich, Katherine; Turner, Drew; Gingell, Imogen; Madanian, Hadi; Gershman, Daniel; Strangeway, Robert
Abstract: Shock waves are common in the heliosphere and beyond. The collisionless nature of most astrophysical plasmas allows for the energy processed by shocks to be partitioned amongst particle sub‐populations and electromagnetic fields via physical mechanisms that are not well understood. The electrostatic potential across such shocks is frame dependent. In a frame where the incident bulk velocity is parallel to the magnetic field, the deHoffmann‐Teller frame, the potential is linked directly to the ambipolar electric field established by the electron pressure gradient. Thus measuring and understanding this potential solves the electron partition problem, and gives insight into other competing shock processes. Integrating measured electric fields in space is problematic since the measurements can have offsets that change with plasma conditions. The offsets, once integrated, can be as large or larger than the shock potential. Here we exploit the high‐quality field and plasma measurements from NASA's Magnetospheric Multiscale mission to attempt this calculation. We investigate recent adaptations of the deHoffmann‐Teller frame transformation to include time variability, and conclude that in practice these face difficulties inherent in the 3D time‐dependent nature of real shocks by comparison to 1D simulations. Potential estimates based on electron fluid and kinetic analyses provide the most robust measures of the deHoffmann‐Teller potential, but with some care direct integration of the electric fields can be made to agree. These results suggest that it will be difficult to independently assess the role of other processes, such as scattering by shock turbulence, in accounting for the electron heating. Plain Language Summary: Shock waves form when a supersonic flow encounters an immovable object. Thus, ahead of the magnetic bubble formed by the Earth's extended magnetic field, the flow of charged particles emanating from the Sun known as the solar wind is shocked, slowed, and deflected around the Earth. In dense fluids, the conversion of the incident bulk flow energy into heat is accomplished by collisions between particles or molecules. However, the solar wind is so rarefied that such collisions are negligible, and the energy conversion involves more than one kinetic process that couples the different particles to the electromagnetic fields. In particular, electric potentials are believed to control the energy split between positive and negative particles. Measuring electric potentials in space is challenging because there is no available zero "earth" potential. In this work, we explore alternative measurements of the potential associated with the electron physics. Some methods can be made to agree with direct determinations using the measured electrons, but we conclude that despite the unprecedented data quality, they are not sufficient to provide an independent determination of the potential. This poses challenges in assessing other, non‐potential physics that also influences the electron energization. Key Points: Measuring directly the cross‐shock deHoffmann‐Teller potential in space is challenging Proposed adaptive frame transformation techniques have limited utility for shocks with 2D or 3D time‐varying structure Electron inferences of the potential are robust but assume scattering is negligible